2000
DOI: 10.1089/10507250050137770
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Hypothyroidism and the Very Low Birthweight Infant

Abstract: Results of thyroid screening tests were examined retrospectively on 311,282 infants born in Massachusetts from January 1, 1993 to December 31, 1996. During this period, 118 infants were found to have typical hypothyroidism, characterized by a low thyroxine (T4) and an elevated thyrotropin (TSH) on the initial newborn-screening specimen. Of these, 98 were normal birthweight (NBW, > or = 2,500 g), 9 were low birthweight (LBW, 1,501-2,499 g), and 11 were very low birthweight (VLBW, < or = 1,500 g). Atypical hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 7 publications
2
66
2
2
Order By: Relevance
“…6,11 In our study, a repeat TSH test detected 19 low or very low birth weight infants with TSH levels >10mIU/L, among whom permanent or transient hypothyroidism was subsequently detected in five. Similar results were obtained by Mandel et al 12 Our observations are also in agreement with data reported by Fisher et al, 6 which showed a prevalence of primary thyroid dysfunction of about 0.5%.…”
Section: Discussionsupporting
confidence: 94%
“…6,11 In our study, a repeat TSH test detected 19 low or very low birth weight infants with TSH levels >10mIU/L, among whom permanent or transient hypothyroidism was subsequently detected in five. Similar results were obtained by Mandel et al 12 Our observations are also in agreement with data reported by Fisher et al, 6 which showed a prevalence of primary thyroid dysfunction of about 0.5%.…”
Section: Discussionsupporting
confidence: 94%
“…NICU, and newborns from multiple births [4,[12][13][14][15][16]. In these situations, the diagnosis of CH-T may be overlooked due to the suppression of the TSH level as a result of various drugs, hypothalamo-pituitary immaturity, and other effects of serious illness [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Although hypothyroidism under these conditions may be self-limiting, it can lead to intellectual disabilities if it is not detected and treated [11]. In addition, FT4 measurement may enable the identification of newborns with CH-T with delayed TSH elevation-found mainly in premature and/or low birth weight (LBW) newborns-who may not be identified by a primary TSH strategy [2,4,[12][13][14].…”
mentioning
confidence: 99%
“…In the study groups with a positive effect of L-thyroxine on the development of preterm babies, a dose of 6-8 μg/kg body weight was used, slightly improving mental development after 5-10 years. However, the greatest problem with decision making is a lack of universal reference values for fT4 and fT3 in preterm newborns [42][43][44][45][46][47][48][49][50][51]. Venous blood TSH values in preterm babies in the first week of life determined with a TSH third-generation test oscillating between 0.7 mIU/l and 27.0 mIU/l [52].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%
“…W dotychczas obserwowanych grupach, w których stwierdzono pozytywny wpływ leczenia L-tyroksyną na rozwój wcześniaków, stosowano dawkę 6-8 μg/kg masy ciała, co powodowało nieco lepszy rozwój umysłowy widoczny po 5-10 latach. Jednak największym problemem przy podejmowaniu decyzji jest brak jednolicie opracowanych wartości referencyjnych fT4 i fT3 u noworodków przedwcześnie urodzonych [42][43][44][45][46][47][48][49][50][51]. Wartości TSH w surowicy krwi żylnej u wcześniaków w pierwszym tygodniu życia oznaczane testem trzeciej generacji oscylują pomiędzy 0,7 mIU/l a 27,0 mIU/l [52].…”
unclassified